(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the scientific and methodological foundations for integrating land cadastre data into investment processes. Based on legal, spatial, and economic indicators of cadastral information, an improved mechanism for assessing the resource base of investment objects is proposed. The results show that the completeness and accuracy of cadastral data enhance the reliability of investment decisions and contribute to reducing costs and risks.